2014
DOI: 10.1051/0004-6361/201424069
|View full text |Cite
|
Sign up to set email alerts
|

Collisions of small ice particles under microgravity conditions

Abstract: Context. Planetisimals are thought to be formed from the solid material of a protoplanetary disk by a process of dust aggregation. It is not known how growth proceeds to kilometre sizes, but it has been proposed that water ice beyond the snowline might affect this process. Aims. To better understand collisional processes in protoplanetary disks leading to planet formation, the individual low velocity collisions of small ice particles were investigated. Methods. The particles were collided under microgravity co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 54 publications
(78 reference statements)
0
28
0
Order By: Relevance
“…Weidling & Blum (2015) performed microgravity experiments with mmsized dust aggregates and found that a coefficient of restitution uniformly distributed in a range between 0.29 and 0.81 with a mean value of 0.55 explains their experiments best. On the other hand, microgravity experiments with mm-to cm-sized ice pebbles have shown that the values for the coefficient of restitution are uniformly distributed between 0.06 and 0.84 with a mean value of 0.45 (Heißelmann et al 2010) or between 0.08 and 0.65 with a mean value of 0.36 (Hill et al 2015). Thus, our choice of coefficient of restitution is in agreement with both types of materials.…”
Section: Coefficient Of Restitution Of Pebblesmentioning
confidence: 57%
See 3 more Smart Citations
“…Weidling & Blum (2015) performed microgravity experiments with mmsized dust aggregates and found that a coefficient of restitution uniformly distributed in a range between 0.29 and 0.81 with a mean value of 0.55 explains their experiments best. On the other hand, microgravity experiments with mm-to cm-sized ice pebbles have shown that the values for the coefficient of restitution are uniformly distributed between 0.06 and 0.84 with a mean value of 0.45 (Heißelmann et al 2010) or between 0.08 and 0.65 with a mean value of 0.36 (Hill et al 2015). Thus, our choice of coefficient of restitution is in agreement with both types of materials.…”
Section: Coefficient Of Restitution Of Pebblesmentioning
confidence: 57%
“…Δv i stick = 10 × Δv d stick , and similarly for bouncing and fragmentation. This factor of ten is motivated by the fact that the specific surface energy and the sticking threshold velocity of water ice is also ten times higher (Gundlach et al 2011;Hill et al 2015). The measured compression curve of ice shown in Fig.…”
Section: Collision Model For Dust and Ice Pebblesmentioning
confidence: 99%
See 2 more Smart Citations
“…But, we can only quantify collisional outcomes empirically, to learn how icy dust sticks under proto-planetary conditions (e.g. Gundlach & Blum 2015;Hill et al 2015;Bridges et al 1996;Higa et al 1996).…”
Section: Introductionmentioning
confidence: 99%